The Identifikasi Bahan Tambahan Makanan (BTM) Pada Lontong, Sosis dan Ayam Potong Yang Diperjualbelikan Di Pasar Antri Cimahi - Pasha, Salsya Islami; Widiyanti Handayani, Rosma; Febrianti, Susan; Wulandari, Novita; Puspita Dewi, Karina; Nurhasanah, Asyifa; Santiaputri, Amalia (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
The supply and demand for food additives cannot be separated from efforts to fulfill the desires and expectations of consumers about the characteristics of a food. However, sometimes business actors use ingredients that are not intended for food to be used in food. Foods that contain Borax, Formalin and Rhodamine B are hazardous materials for the body, contain preservatives and foods that contain harmful dyes. Misuse of borax in food is usually intended as a hardener, chewing agent, and preservative. Formalin is used as a germ killer so that it is used as an insect repellent and corpse preservative. While Rhodamine B dyes are carcinogenic. Used as a dye for paper, textiles (silk, wool, cotton), and soap. This study aims to identify and find out more about the content of Food Additives (BTM) which are traded freely in the cimahi queuing market. This type of research uses qualitative methods by conducting laboratory tests. The results of this study indicate the presence of food additives in some samples used, which means that the use of prohibited BTM is still used freely by some traders in the market. This allows for potential harm to the health of the surrounding community as consumers due to continuous consumption of food containing BTM.